Peran Kebijakan Lokal dalam Mendukung Keberlanjutan Usaha Perikanan Tradisional - Padang, Allan; Anjasmoro, Dadang Fery; Kurniah, Asih (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Traditional fisheries play a crucial role in supporting local economies, especially in coastal areas, and contribute to national food security. However, this sector faces numerous challenges, such as climate change, overfishing, and limited market access. This study aims to identify the role of local policies in supporting the sustainability of traditional fisheries and provide strategic recommendations. Using a descriptive qualitative method, data were collected through in-depth interviews, direct observation, and document studies in coastal communities. The results reveal that inclusive local policies, technical support, and fishermen empowerment can enhance the sustainability of this sector. However, challenges such as limited resources, weak oversight, and low community participation need to be addressed through multi-stakeholder collaboration. This study recommends enhancing fishermen's capacities, strengthening market access, and implementing community-based marine resource management to achieve long-term sustainability.